(untitled) (Scientific journal of the Fergana State University, 2023)
The article is based on the poem ‘’ If this known the flowers …’’ by H. Hayne, the poet draws on scientific analysis of the lyrical protagonist’s inner experiences of suffering and feeling through various images.